Positive electrode for lithium-sulfur battery and lithium-sulfur battery including the same

The introduction of island-shaped carbon coating layers on the sulfur-carbon composite in lithium-sulfur batteries enhances electrochemical reactivity, addressing conductivity issues and improving battery performance and stability.

JP7612853B2Active Publication Date: 2025-01-14LG ENERGY SOLUTION LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023521948
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-07-07
Filing Date
2022-07-08
Publication Date
2025-01-14
Estimated Expiration
2042-07-08

AI Technical Summary

Technical Problem

Lithium-sulfur batteries face challenges with low electrical conductivity of sulfur, leading to reduced electrochemical reactivity and rapid capacity and efficiency decline due to lithium polysulfide seepage, which affects their performance and stability.

Method used

A positive electrode for lithium-sulfur batteries is developed with a sulfur-carbon composite having numerous island-shaped carbon coating layers to increase electrochemical reaction sites, enhancing conductivity and reactivity.

Benefits of technology

The solution improves the electrochemical reactivity and stability of the positive electrode, resulting in higher capacity and energy density, and better cycle life characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612853000004
    Figure 0007612853000004
  • Figure 0007612853000005
    Figure 0007612853000005
  • Figure 0007612853000006
    Figure 0007612853000006
Patent Text Reader

Abstract

The present invention relates to a lithium-sulfur battery cathode including a sulfur-carbon composite having a surface coated with a carbon layer in the form of multiple islands, and a lithium-sulfur battery including the cathode. The cathode for a lithium-sulfur battery according to the present invention has excellent electrochemical reactivity, enabling the lithium-sulfur battery including the cathode to have high capacity, high power output, and long life.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0090243 filed on July 9, 2021 and Korean Patent Application No. 10-2022-0083460 filed on July 7, 2022, and all contents disclosed in the documents of the relevant Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a positive electrode for a lithium-sulfur battery and a lithium-sulfur battery including the same. [Background technology]

[0003] The range of applications of lithium secondary batteries has expanded from portable electronic devices and communication devices to electric vehicles (EVs) and electric storage systems (ESSs), and there has been an increasing demand for higher capacity lithium secondary batteries used as power sources for these devices.

[0004] Among the various lithium secondary batteries, the lithium-sulfur battery is a battery system that uses a sulfur-based material containing a sulfur-sulfur bond as the positive electrode active material, and lithium metal, a carbon-based material in which lithium ions are inserted / deinserted, or silicon or tin that forms an alloy with lithium as the negative electrode active material.

[0005] Sulfur, the main positive electrode active material in lithium-sulfur batteries, has the advantages of being low weight per unit atom, abundant in resources, easy to supply and demand, inexpensive, non-toxic, and environmentally friendly.

[0006] In addition, lithium-sulfur batteries undergo a conversion reaction between lithium ions and sulfur at the positive electrode (S8+16Li + +16e ‐The theoretical discharge capacity of lithium-ion batteries (Li-FeS, Li-MnO2, Na-S) is 1,675mAh / g, and when lithium metal (theoretical capacity: 3,860mAh / g) is used in the negative electrode, it shows a theoretical energy density of 2,600Wh / kg. This is a much higher value than the theoretical energy density of other battery systems currently being researched (Ni-MH battery: 450Wh / kg, Li-FeS battery: 480Wh / kg, Li-MnO2 battery: 1,000Wh / kg, Na-S battery: 800Wh / kg) and lithium-ion batteries (250Wh / kg), so it is attracting attention as a high-capacity, environmentally friendly, and low-cost lithium secondary battery among the secondary batteries developed to date, and several studies are being conducted on next-generation battery systems.

[0007] In lithium-sulfur batteries, the sulfur used as the positive electrode active material has an electrical conductivity of 5×10 ‐30 Since sulfur is an insulator with no electrical conductivity at 1000 S / cm, it is difficult to move electrons generated in electrochemical reactions. Therefore, sulfur-carbon composites are used by combining it with carbon materials that can provide electrochemical reaction sites.

[0008] However, lithium polysulfide (Li2S) is generated during the charge and discharge process of lithium-sulfur batteries. x In addition to the problem of the seepage of sulfur (x = 8, 6, 4, 2), there is also the problem of reduced electrochemical reactivity of the sulfur-carbon composite, which is the positive electrode active material, due to the low electrical conductivity of sulfur, which is the positive electrode active material, and lithium sulfide (Li2S), which is a discharge product of sulfur.

[0009] As a result, although lithium-sulfur batteries have a high initial discharge capacity during actual operation, as the cycle progresses, the capacity and charge / discharge efficiency characteristics rapidly decrease, and as a result, the energy density and life characteristics also decrease, so it is difficult to ensure sufficient performance and operating stability, and the battery has not been put to commercial use.

[0010] In order to realize a lithium-sulfur battery with a commercially viable level of energy density and life characteristics, various technologies have been proposed to improve the electrochemical reactivity of the positive electrode, specifically, the sulfur-carbon composite that is the positive electrode active material.

[0011] For example, Korean Patent Publication No. 2016-0046775 discloses that a positive electrode coating layer made of an amphiphilic polymer is provided on a surface of a part of a positive electrode active part including a sulfur-carbon composite to suppress the outflow of lithium polysulfide, thereby improving the cycle characteristics of a lithium-sulfur battery.

[0012] Although the coating layers proposed in these patents have improved the lithium polysulfide leakage problem to some extent, they are not effective enough in maintaining the electrochemical reactivity of the positive electrode. In addition, the manufacturing process is complicated and the materials used are expensive, making them unsuitable for commercialization. Therefore, there is still a need to develop a lithium-sulfur battery that can improve the electrochemical reactivity of the positive electrode through a simple process and realize excellent performance and driving stability. [Prior art documents] [Patent documents]

[0013] [Patent Document 1] Korean Patent Publication No. 2016-0046775 (April 29, 2016), Positive electrode for lithium-sulfur battery and manufacturing method thereof Summary of the Invention [Problem to be solved by the invention]

[0014] Here, the present inventors have conducted extensive research to solve the above problem, and have found that when an island-shaped carbon coating layer is introduced onto the surface of a sulfur-carbon composite, the number of electrochemical reaction sites is increased, thereby improving electrochemical reactivity, thereby completing the present invention.

[0015] SUMMARY OF THE PRESENT EMBODIMENTS Accordingly, an object of the present invention is to provide a positive electrode for a lithium-sulfur battery having excellent electrochemical reactivity.

[0016] Another object of the present invention is to provide a lithium-sulfur battery including the positive electrode. [Means for solving the problem]

[0017] To achieve the above object, the present invention provides a positive electrode for a lithium-sulfur battery, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer comprising a sulfur-carbon composite having a plurality of island-shaped carbon coating layers on a surface thereof as a positive electrode active material.

[0018] The present invention also provides a lithium-sulfur battery comprising the positive electrode for a lithium-sulfur battery. Effect of the Invention

[0019] The positive electrode for a lithium-sulfur battery according to the present invention includes a sulfur-carbon composite including a plurality of carbon coating layers distributed in a discontinuous island shape on the surface as a positive electrode active material, and thus the number of electrochemical reaction sites is increased, resulting in excellent electrochemical reactivity of the positive electrode. As a result, the capacity expression of the positive electrode can be maximized, and a lithium-sulfur battery having high capacity and high energy density can be realized. [Brief description of the drawings]

[0020] [Figure 1] 1 is a diagram simply illustrating a configuration of a positive electrode active material layer according to an example of the present invention. [Diagram 2] 1 is a scanning electron microscope photograph of a positive electrode according to Example 3. [Diagram 3] 1 is a scanning electron microscope photograph of a positive electrode according to Example 6. [Figure 4] 1 is a scanning electron microscope photograph of a positive electrode according to Comparative Example 2. [Diagram 5]13 is a graph showing the results of evaluating the capacity characteristics of a lithium-sulfur battery according to Experimental Example 3. [Figure 6] 13 is a graph showing the results of evaluating the capacity characteristics of a lithium-sulfur battery according to Experimental Example 3. [Figure 7] 13 is a graph showing the results of evaluating the life characteristics of a lithium-sulfur battery according to Experimental Example 3. [Figure 8] 13 is a graph showing the results of evaluating the life characteristics of a lithium-sulfur battery according to Experimental Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention will now be described in more detail.

[0022] The terms and words used in this specification and claims should not be construed in a limited manner based on their ordinary or dictionary meaning, but should be interpreted in a meaning and concept that corresponds to the technical idea of ​​the present invention, based on the principle that the inventor can appropriately define the concept of the term in order to explain his / her invention in the best possible way.

[0023] The terms used in the present invention are merely used to describe specific embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In the present invention, the terms "include" or "have" specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.

[0024] As used herein, the term "composite" refers to a material in which two or more materials are combined to form physically and chemically distinct phases, thereby exhibiting a more effective function.

[0025] As used herein, the term "polysulfide" means "polysulfide ion (S x 2‐ , x=8, 6, 4, 2)) and Lithium polysulfide (Li2S x or LiS x ‐ , x=8, 6, 4, 2) is a concept that includes all of these.

[0026] As used herein, the term "mean volume diameter (MV)" refers to the arithmetic mean particle size measured by volume, and is used interchangeably with "average particle size (D 10 ) is the particle size at 10% of the cumulative particle size distribution by volume, and "average particle size (D 50 ) can be defined as the particle size at 50% of the volume cumulative particle size distribution, and can be measured using the laser diffraction method.

[0027] Lithium-sulfur batteries are in the spotlight as a next-generation secondary battery due to their high discharge capacity and theoretical energy density, as well as the advantages of low battery manufacturing costs and environmental friendliness, as sulfur, which is used as a positive electrode active material, is abundant and inexpensive.

[0028] In lithium-sulfur batteries, sulfur, which is a positive electrode active material, is a non-conductor and is used in the form of a sulfur-carbon composite in which sulfur is combined with a conductive carbon material to supplement electrical conductivity.

[0029] However, lithium-sulfur batteries suffer from the loss of sulfur that participates in the electrochemical reaction due to the emergence of lithium polysulfide generated during charging and discharging, and the electrochemical reactivity of the sulfur-carbon composite, which is the positive electrode active material, is reduced due to the very low electrical conductivity of lithium sulfide, which is a sulfur reduction material, resulting in the problem that the theoretical discharge capacity and theoretical energy density cannot be fully realized in actual operation, and the deterioration of battery performance and driving stability is accelerated.In addition, sulfur is converted into lithium sulfide, causing about 80% volume expansion, which reduces the volume of the voids inside the positive electrode and makes it difficult to contact the electrolyte, further reducing the electrochemical reactivity of the positive electrode active material.

[0030] For this reason, in the prior art, methods have been proposed such as increasing the sulfur loading amount, using a carbon material with a high specific surface area as a sulfur carrier, and introducing a coating layer to suppress the leaching of lithium polysulfide. However, these methods have not effectively improved the performance of lithium-sulfur batteries, and still have serious problems with battery stability and are inefficient in terms of processing.

[0031] Here, the present invention provides a lithium-sulfur battery cathode that can realize a lithium-sulfur battery having improved capacity, output, and life characteristics by forming an island-shaped discontinuous carbon coating layer on the surface of a sulfur-carbon composite as a carbon material having a high specific surface area, thereby increasing reaction sites where electrochemical oxidation-reduction reactions can occur and improving the electrochemical reactivity of the cathode.

[0032] Specifically, the positive electrode for a lithium-sulfur battery according to the present invention includes a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector, and the positive electrode active material layer includes a sulfur-carbon composite having a plurality of island-shaped carbon coating layers on a surface thereof as a positive electrode active material. Here, the island shape means that the carbon coating layer is distributed on the surface of the sulfur-carbon composite in a discontinuous manner like islands, and the shape of each island-shaped carbon coating layer present at a distance is not particularly limited, and may have various shapes such as a sphere, a cylinder, a polygonal column, a hemisphere, an ellipse, an irregular shape, etc.

[0033] FIG. 1 shows a simplified structure of a cathode active material layer according to an embodiment of the present invention. As shown in FIG. 1, the cathode active material included in the cathode active material layer of the present invention has a sulfur-carbon composite 11 having a discontinuous island-shaped carbon coating layer 13 distributed on the surface. In the present invention, a powder-like carbon material having a high specific surface area is dispersed in a dispersion medium without using a separate dispersant and mixed with a sulfur-carbon composite or a cathode slurry composition containing the same, and the sulfur-carbon composite having a carbon coating layer distributed discontinuously in an island shape on the surface is included as a cathode active material in the cathode active material layer, specifically, in the cathode active material layer. As a result, the cathode active material included in the cathode active material layer has a high specific surface area, and the number of reaction sites for oxidation and reduction is increased, thereby improving electrochemical reactivity, and a lithium-sulfur battery having excellent capacity, output, and life characteristics can be realized.

[0034] In the present invention, the positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on one or both sides of the positive electrode current collector.

[0035] The positive electrode current collector is not particularly limited as long as it supports the positive electrode active material layer, does not cause chemical changes in the battery, and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, palladium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, silver, etc., aluminum-cadmium alloy, etc. may be used.

[0036] The positive electrode current collector may have fine irregularities on its surface to strengthen the bonding force with the positive electrode active material, and may be in various forms such as a film, a sheet, a foil, a mesh, a net, a porous body, a foam, a nonwoven fabric, etc.

[0037] The positive electrode active material layer includes a sulfur-carbon composite having a carbon coating layer in the form of multiple islands on the surface thereof as a positive electrode active material.

[0038] The sulfur-carbon composite includes a porous carbon material and sulfur in at least a portion of the interior and exterior surfaces of the porous carbon material. Since sulfur does not have electrical conductivity by itself, it is used in combination with a conductive material, thereby forming a sulfur-carbon composite.

[0039] The sulfur may include at least one selected from the group consisting of elemental sulfur (S8) and sulfur compounds. The positive electrode active material may include inorganic sulfur, Li2S n (n≧1), disulfide compounds, organic sulfur compounds and carbon-sulfur polymers ((C2S x ) n , x=2.5 to 50, n≧2). Preferably, the sulfur is inorganic sulfur.

[0040] The sulfur may be included in an amount of 60 to 90 wt%, preferably 65 to 80 wt%, based on 100 wt% of the total positive electrode active material layer. If the sulfur content in the positive electrode active material layer is less than 60 wt%, there is a limit to increasing the energy density of the battery.

[0041] The porous carbon material not only provides a framework to which the sulfur can be uniformly and stably fixed, but also complements the low electrical conductivity of sulfur, allowing the electrochemical reaction to proceed smoothly.

[0042] The porous carbon material may be any carbon-based material commonly used in the art that has conductivity, a porous structure, or a high specific surface area. For example, the porous carbon material may be at least one selected from the group consisting of graphite, graphene, carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs), carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs), graphite such as natural graphite, artificial graphite, and expanded graphite, and activated carbon.

[0043] The porous carbon material may be prepared by carbonizing various carbon precursors and may contain a large number of pores on the surface and inside. The average diameter of the pores is in the range of 1 to 200 nm, and the porosity is in the range of 10 to 90% of the total volume of the porous carbon material. If the average diameter of the pores is less than the range, the size of the pores is merely at the molecular level, making it impossible to impregnate with sulfur, and conversely, if the average diameter of the pores is more than the range, the mechanical strength of the porous carbon material is weakened, making it unsuitable for use in the manufacturing process of a positive electrode.

[0044] The porous carbon material has an average diameter of 100 nm to 50 μm, preferably 10 to 50 μm. If the average diameter of the porous carbon material is less than this range, there may be a problem in supporting sulfur in the pores of the porous carbon material, and conversely, if it exceeds this range, the conductivity of the sulfur-carbon composite may decrease.

[0045] The shape of the porous carbon material may be any shape commonly used in lithium-sulfur batteries, such as a sphere, rod, needle, plate, tube, or bulk, without any limitation.

[0046] In the sulfur-carbon composite of the present invention, the sulfur is located at least in one of the interior and surface of the porous carbon material, and may be present in less than 100%, preferably 1 to 95%, more preferably 60 to 90% of the entire interior and exterior surface of the porous carbon material. When the sulfur is present in the above range in the interior and exterior surface of the porous carbon material, the maximum effect can be exhibited in terms of the electron transfer area and wettability with the electrolyte. Specifically, in the above range, the sulfur is thinly and uniformly impregnated in the interior and exterior surfaces of the porous carbon material, thereby increasing the electron transfer contact area during charging and discharging. If the sulfur is located in 100% of the interior and exterior surface of the porous carbon material, the porous carbon material is completely covered with sulfur, which reduces the wettability with the electrolyte and prevents electron transfer and participation in the electrochemical reaction.

[0047] The sulfur-carbon composite may contain 65 to 90 wt %, preferably 70 to 85 wt %, and more preferably 72 to 80 wt %, of the sulfur, based on 100 wt % of the total sulfur-carbon composite. If the sulfur content is less than the above range, the content of the porous carbon material in the sulfur-carbon composite increases relatively, and the content of the binder used in manufacturing the positive electrode increases. This increase in the amount of binder used may ultimately increase the surface resistance of the positive electrode and act as an insulator that prevents electron pass, thereby reducing the battery performance. On the other hand, if the sulfur content exceeds the above range, the sulfur that cannot be bonded to the porous carbon material may gather together or be re-sprouted on the surface of the porous carbon material, making it difficult for the sulfur to receive electrons and participate in the electrochemical reaction, resulting in a loss of battery capacity.

[0048] Accordingly, in the sulfur-carbon composite of the present invention, the weight ratio of the porous carbon material to sulfur (weight % of the porous carbon material:weight % of sulfur) is 35:65 to 10:90, preferably 30:70 to 15:85.

[0049] The sulfur-carbon composite may be a composite of the sulfur and the porous carbon material by simply mixing, or may have a core-shell structure coating or support. The core-shell structure coating form is a form in which either the sulfur or the porous carbon material is coated with the other material, for example, the surface of the porous carbon material may be wrapped with sulfur, or vice versa. The support form is a form in which sulfur is supported inside the porous carbon material. The sulfur-carbon composite may be in any form as long as it satisfies the content ratio of sulfur to the porous carbon material, and is not limited in the present invention.

[0050] The method for preparing the sulfur-carbon composite is not particularly limited in the present invention, and may be a method commonly used in the art. For example, the porous carbon material and sulfur may be simply mixed and then heat-treated to prepare a composite.

[0051] The sulfur-carbon composite may be included in an amount of 70 to 100 wt %, preferably 85 to 98 wt %, based on the total weight of the positive electrode active material layer. If the content of the sulfur-carbon composite is less than this range, the relative content of additional components such as binders increases, making it difficult to realize a battery with high capacity and high energy density. Conversely, if the content exceeds this range, the relative content of binders is insufficient, resulting in a problem of deterioration of the physical properties of the positive electrode.

[0052] The carbon coating layer is distributed in an island shape on the surface of the sulfur-carbon composite and includes reduced graphene oxide (rGO).

[0053] The reduced graphene oxide has a specific surface area of ​​700 m 2 / g or more, preferably 700 to 1500m 2 / g, more preferably 800 to 1000m 2 / g.

[0054] The reduced graphene oxide may be included in an amount of 0.5 to 3 wt%, preferably 0.7 to 1.5 wt%, based on the total weight of the positive electrode active material. If the content of the reduced graphene oxide is less than this range, the amount of the carbon coating layer is too small to achieve the intended effect. Conversely, if the content of the reduced graphene oxide is more than this range, the carbon coating layer is formed over a very wide area, which may cause a problem of a significant increase in initial resistance.

[0055] The size of the island shape of the carbon coating layer is not limited thereto, but for example, the average length in the longitudinal direction is 10 to 100 μm, preferably 20 to 80 μm, and more preferably 30 to 70 μm. At this time, the method for measuring the longitudinal length of the island-shaped carbon coating layer is not particularly limited, and a method known in the field of lithium secondary battery technology may be used. If the size of the island shape is too large, the surface of the sulfur-carbon composite may be too blocked, so that the initial resistance may increase rapidly, and if the size of the island shape is too small, the effect of forming the carbon coating layer on the sulfur-carbon composite may be insufficient. If the size of the island shape of the carbon coating layer satisfies the above range, the electrochemical reactivity improvement effect due to the formation of the carbon coating layer may be ensured without deteriorating the operation or performance of the battery.

[0056] As described above, the cathode active material of the present invention, which includes a plurality of island-shaped carbon coating layers on the surface of the sulfur-carbon composite, exhibits improved specific surface area and pore volume and includes small pores compared to a sulfur-carbon composite that does not include a carbon coating layer (hereinafter, referred to as a pure sulfur-carbon composite).

[0057] Specifically, the positive electrode active material has a specific surface area of ​​20 to 50 m 2 / g, preferably 30 to 40m 2The positive electrode active material has a pore volume of 0.3 to 0.5 cm. 3 / g, preferably 0.35 to 0.45 cm 3 In addition, the positive electrode active material may include pores having a size ranging from 30 to 70 nm.

[0058] In addition, since the positive active material includes the carbon coating layer, the volume average particle size and average particle size tend to be reduced compared to the pure sulfur-carbon composite.

[0059] Specifically, the positive electrode active material has a volume average particle diameter of 30 to 70 μm, preferably 40 to 65 μm. 10 ) is 5 to 30 μm, preferably 10 to 20 μm, and the average particle size (D 50 ) is 30 to 60 μm, preferably 40 to 55 μm.

[0060] On the other hand, when a continuous carbon coating layer is included on the entire surface of the sulfur-carbon composite, the basal plane of the reduced graphene oxide included in the carbon coating layer covers the surface, so that the final cathode active material (sulfur-carbon composite entirely coated with a carbon coating layer) has a lower specific surface area than that of a pure sulfur-carbon composite.

[0061] Thus, in the cathode active material of the present invention including a plurality of island-shaped carbon coating layers discontinuously formed on the surface of the sulfur-carbon composite, the ratio of the specific surface area of ​​the cathode active material of the present invention to the specific surface area of ​​the pure sulfur-carbon composite (specific surface area of ​​the cathode active material of the present invention / specific surface area of ​​the pure sulfur-carbon composite) is 1 or more, preferably 1 to 3, and more preferably 1.5 to 2.7.

[0062] The cathode active material according to the present invention includes a carbon coating layer formed in a discontinuous island shape on the surface of the sulfur-carbon composite, thereby decreasing the average particle size, increasing the specific surface area and pore volume, and increasing the number of sites where an electrochemical reaction can proceed, thereby exhibiting excellent electrochemical reactivity, and thus ensuring an effect of improving the capacity, output, and life characteristics of a lithium-sulfur battery.

[0063] Referring to FIG. 1, the positive electrode active material layer of the present invention may further include a carbon bridge 15 in addition to the positive electrode active material described above.

[0064] The carbon bridge is an aggregate of reduced graphene oxide that could not form a carbon coating layer on the surface of the sulfur-carbon composite, and serves as a bridge connecting the positive active materials. In addition, since the positive active material layer of the present invention includes the carbon bridge, it does not include a separate conductive material.

[0065] The carbon bridge may have any shape as long as it can exist in the voids in the positive electrode active material layer of the present invention, specifically between the positive electrode active materials. For example, the carbon bridge may have one or more shapes selected from a crumpled structure, an amorphous shape, a plate shape, a flake shape, a spherical shape, and a fiber shape.

[0066] The positive electrode active material layer of the present invention may further include, in addition to the positive electrode active material, one or more additives selected from a transition metal element, a Group IIIA element, a Group IVA element, sulfur compounds of these elements, and alloys of these elements with sulfur.

[0067] The transition metal elements include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au, or Hg, and the IIIA group elements include Al, Ga, In, or Tl, and the IVA group elements include Ge, Sn, or Pb.

[0068] The positive electrode active material layer may further include a binder for better adhering the positive electrode active material to a current collector, in addition to the positive electrode active material and the carbon bridge, or optionally, the additive.

[0069] The binder supports the positive electrode active material on the positive electrode current collector and organically connects the positive electrode active materials to enhance the binding strength therebetween, and any binder known in the art may be used.

[0070] For example, the binder may be one or a mixture or copolymer of two or more selected from the group consisting of fluororesin-based binders including polyvinylidene fluoride (PVdF) or polytetrafluoroethylene (PTFE); rubber-based binders including styrene butadiene rubber (SBR), acrylonitrile butadiene rubber, and styrene-isoprene rubber; cellulose-based binders including carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose; polyalcohol-based binders; polyolefin-based binders including polyethylene and polypropylene; polyimide-based binders; polyester-based binders; and silane-based binders.

[0071] The binder may be included in an amount of 0.5 to 30 wt % based on the total weight of the positive electrode active material layer. If the content of the binder is less than this range, the physical properties of the positive electrode may be deteriorated and the positive electrode active material may be detached from the positive electrode, and if the content exceeds this range, the proportion of the positive electrode active material in the positive electrode may be relatively reduced and the battery capacity may be reduced. Therefore, it is preferable to determine the appropriate content within the above range.

[0072] In the present invention, the method for manufacturing the positive electrode for the lithium-sulfur battery is not particularly limited, and any method known to those skilled in the art or various methods modified therefrom may be used.

[0073] For example, the positive electrode for the lithium-sulfur battery may be manufactured by preparing a positive electrode slurry composition including the above-mentioned composition, and then coating the positive electrode slurry composition on at least one surface of the positive electrode current collector to form a positive electrode active material layer.

[0074] The positive electrode slurry composition includes the positive electrode active material, binder, additives, etc., and may further include a solvent.

[0075] According to an embodiment of the present invention, the positive electrode slurry composition may be prepared by dispersing reduced graphene oxide in a dispersion medium to prepare a reduced graphene oxide dispersion; mixing the reduced graphene oxide dispersion with a sulfur-carbon composite and drying the mixture to prepare a sulfur-carbon composite having a plurality of island-shaped carbon coating layers on a surface thereof; and mixing the sulfur-carbon composite having the carbon coating layers with a binder, an additive, and a solvent.

[0076] According to another embodiment of the present invention, the positive electrode slurry composition may be prepared by preparing a pre-dispersion containing reduced graphene oxide, and then adding (externally adding) the pre-dispersion to a mixture containing a sulfur-carbon composite, a binder solvent, etc. When preparing the pre-dispersion, reduced graphene oxide may be dispersed in a binder.

[0077] The dispersion medium used to prepare the reduced graphene oxide dispersion may be a lower alcohol such as ethanol.

[0078] The solvent is one that can uniformly disperse the positive electrode active material, binder, and additives. The solvent is most preferably water, which is an aqueous solvent, and in this case, the water is distilled water or deionized water. However, the solvent is not necessarily limited thereto, and if necessary, a lower alcohol that can be easily mixed with water can be used. The lower alcohol includes methanol, ethanol, propanol, isopropanol, butanol, etc., and preferably, these can be mixed with water before use.

[0079] The content of the solvent may be at a level having a concentration that can facilitate application of the positive electrode slurry composition, and the specific content varies depending on the application method and device.

[0080] The positive electrode slurry composition may further include, as necessary, a substance commonly used in the relevant technical field for the purpose of improving its function, etc., such as a viscosity modifier, a fluidizing agent, a filler, etc.

[0081] The method of applying the positive electrode slurry composition is not particularly limited in the present invention, and may include, for example, methods such as doctor blade, die casting, comma coating, screen printing, etc. In addition, the positive electrode slurry may be applied onto the positive electrode current collector by a pressing or lamination method after forming the positive electrode slurry on a substrate separately.

[0082] After the coating, a drying process may be performed to remove the solvent. The drying process is performed at a temperature and time level that allows the solvent to be sufficiently removed, and the conditions may vary depending on the type of solvent, and are not particularly limited in the present invention. Examples include drying with warm air, hot air, or low humidity air, vacuum drying, and drying by irradiation with (far) infrared rays and electron beams. The drying speed is usually adjusted so that the solvent can be removed as quickly as possible within a speed range that does not cause cracks in the positive electrode active material layer due to stress concentration or the positive electrode active material layer to peel off from the positive electrode current collector.

[0083] The present invention also provides a lithium-sulfur battery comprising the positive electrode for a lithium-sulfur battery.

[0084] The lithium-sulfur battery includes a positive electrode, a negative electrode, and an electrolyte interposed therebetween, and the positive electrode includes the positive electrode for a lithium-sulfur battery according to the present invention.

[0085] The positive electrode is according to the invention and is in accordance with the above description.

[0086] The negative electrode may include a negative electrode current collector and a negative electrode active material layer coated on one or both sides of the negative electrode current collector, or the negative electrode may be a lithium metal plate.

[0087] The negative electrode current collector is for supporting the negative electrode active material layer, and is the same as that described for the positive electrode current collector.

[0088] The negative active material layer may further include a negative active material, a conductive material, a binder, and the like, and the conductive material and the binder are the same as those described above.

[0089] The negative electrode active material is lithium (Li + The lithium-containing compound may include a material capable of reversibly intercalating or deintercalating lithium ions, a material capable of reversibly reacting with lithium ions to form a lithium-containing compound, lithium metal, or a lithium alloy.

[0090] The lithium ion (Li + The material capable of reversibly inserting or de-inserting lithium ions (Li) is, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + The material capable of reacting with lithium (Li) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitride, or silicone. The lithium alloy is, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).

[0091] Preferably, the negative electrode active material is lithium metal, and specifically, may be in the form of a lithium metal thin film or lithium metal powder.

[0092] The method for manufacturing the negative electrode is not particularly limited, and may be a layer or film forming method commonly used in the art, such as squeezing, coating, deposition, etc. In addition, the negative electrode of the present invention may also include a case where a thin lithium film is formed on a metal plate by initial charging after assembling a battery without a thin lithium film on a current collector.

[0093] The electrolyte is disposed between the positive and negative electrodes and serves to cause an electrochemical oxidation or reduction reaction between the positive and negative electrodes through the electrolyte, and includes a lithium salt and a non-aqueous organic solvent.

[0094] The lithium salt can be any that can be generally used in lithium secondary batteries without any limitations.

[0095] Specific examples of the lithium salt include LiCl, LiBr, LiI, LiClO4, LiBF4, and LiB 10 Cl 10, LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, LiSO3CH3, LiSO3CF3, LiSCN, LiC(CF3SO2)3, LiN(CF3SO2)2 (lithium bis(trifluoromethanesulfonyl)imide; LiTFSI), LiN(C2F5SO2)2, LiN(SO2F)2 (lithium bis(fluorosulfonyl)imide; LiFSI), lithium chloroborane, lithium lower aliphatic carboxylates, lithium tetraphenylborate, and lithium imide.

[0096] The concentration of the lithium salt is 0.2 to 4 M, specifically 0.6 to 2 M, more specifically 0.7 to 1.7 M, depending on various factors such as the composition of the electrolyte, the solubility of the lithium salt, the conductivity of the dissolved lithium salt, the charging and discharging conditions of the battery, the operating temperature, and other factors known in the field of lithium secondary batteries. If the lithium salt is used at a concentration of less than 0.2 M, the conductivity of the electrolyte may decrease, resulting in a decrease in electrolyte performance, and if the concentration exceeds 4 M, the viscosity of the electrolyte may increase, resulting in a decrease in the mobility of lithium ions.

[0097] The non-aqueous organic solvent may be any organic solvent commonly used in electrolytes for lithium secondary batteries without limitation. For example, the organic solvent may be ether, ester, amide, linear carbonate, cyclic carbonate, etc., which may be used alone or in combination of two or more. Among them, ether-based compounds may be representatively used.

[0098] As an example, the ether-based compound may be at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, methoxyethoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, polyethylene glycol methyl ethyl ether, 1,3-dioxolane, tetrahydrofuran, and 2-methyltetrahydrofuran, but is not limited thereto.

[0099] Among the organic solvents, the ester may be any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone, or a mixture of two or more of these may be used, but is not limited thereto.

[0100] Specific examples of the linear carbonate compound include, but are not limited to, any one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, or a mixture of two or more of these.

[0101] Specific examples of the cyclic carbonate compound include any one or mixtures of two or more selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate, and halides thereof. Examples of halides thereof include, but are not limited to, fluoroethylene carbonate (FEC).

[0102] In addition to the above organic solvents, the solvent may contain one or more selected from the group consisting of N-methylpyrrolidone, dimethyl sulfoxide, sulfolane furan, 2-methylfuran, 3-methylfuran, 2-ethylfuran, 2-propylfuran, 2-butylfuran, 2,3-dimethylfuran, 2,4-dimethylfuran, 2,5-dimethylfuran, pyran, 2-methylpyran, 3-methylpyran, 4-methylpyran, benzofuran, 2-(2-nitrovinyl)furan, thiophene, 2-methylthiophene, 2-ethylthiophene, 2-propylthiophene, 2-butylthiophene, 2,3-dimethylthiophene, 2,4-dimethylthiophene, and 2,5-dimethylthiophene.

[0103] In addition to the above-mentioned composition, the electrolyte may further include a nitrate-based compound commonly used in the relevant technical field, such as lithium nitrate (LiNO3), potassium nitrate (KNO3), cesium nitrate (CsNO3), magnesium nitrate (Mg(NO3)2), barium nitrate (Ba(NO3)2), lithium nitrite (LiNO2), potassium nitrite (KNO2), cesium nitrite (CsNO2), etc.

[0104] The electrolyte injection may be performed at a suitable stage during the battery manufacturing process depending on the manufacturing process and required properties of the final product, i.e., before or at the final stage of battery assembly.

[0105] A separator may further be included between the positive electrode and the negative electrode.

[0106] The separator separates or insulates the positive electrode and the negative electrode from each other and allows lithium ions to be transported between the positive electrode and the negative electrode, and may be made of a porous non-conductive or insulating material, and may be any material that is generally used as a separator in lithium secondary batteries without any particular limitations. Such a separator may be an independent member such as a film, or may be a coating layer added to the positive electrode and / or the negative electrode.

[0107] The separation membrane is preferably one that has low resistance to the ion migration of the electrolyte and has excellent moisture-absorbing capacity for the electrolyte.

[0108] The separator may be made of a porous substrate, and the porous substrate may be any porous substrate typically used in secondary batteries. A porous polymer film may be used alone or in combination. For example, a nonwoven fabric or a polyolefin-based porous membrane made of high-melting-point glass fiber, polyethylene terephthalate fiber, or the like may be used, but is not limited thereto.

[0109] The material of the porous substrate is not particularly limited in the present invention, and any porous substrate generally used in electrochemical devices can be used. For example, the porous substrate can be a polyolefin such as polyethylene or polypropylene, a polyester such as polyethylene terephthalate or polybutylene terephthalate, a polyamide, a polyacetal, a polycarbonate, a polyimide, a polyether ether ketone, a polyether sulfone, a polyphenylene oxide, a polyphenylene sulfide, a polyethylene naphthalene, a polytetrafluoroethylene, a polyvinylidene fluoride, a polyvinyl chloride, or the like. The material may include one or more materials selected from the group consisting of poly(p-phenylene benzobisoxazole), polyacrylonitrile, cellulose, nylon, poly(p-phenylene benzobisoxazole), and polyarylate.

[0110] The thickness of the porous substrate is not particularly limited, but is 1 to 100 μm, preferably 5 to 50 μm. The thickness range of the porous substrate is not limited to the above range, but if the thickness is smaller than the above lower limit, the mechanical properties may be deteriorated and the separator may be easily damaged during use of the battery.

[0111] The average diameter and porosity of the pores in the porous substrate are not particularly limited, but are in the range of 0.001 to 50 μm and 10 to 95%, respectively.

[0112] The lithium-sulfur battery of the present invention can be classified into cylindrical, prismatic, coin, pouch, etc. according to shape, and into bulk type and thin film type according to size. The structure and manufacturing method of these batteries are widely known in the art, so a detailed description will be omitted.

[0113] The present invention also provides a battery module including the lithium-sulfur battery as a unit cell.

[0114] The battery module can be used as a power source for medium to large size devices that require high temperature stability, long cycle characteristics, and high capacity characteristics.

[0115] Examples of the medium- to large-sized devices include, but are not limited to, power tools that are powered by battery-powered motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.

[0116] In the following, preferred examples are presented to facilitate understanding of the present invention. However, the following examples are merely illustrative of the present invention, and it will be obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention. It is natural that such changes and modifications fall within the scope of the accompanying claims.

[0117] Examples and Comparative Examples [Example 1] Specific surface area is 1000m 2 A pre-dispersion was prepared by mixing reduced graphene oxide (0.1 g / g) and a binder (styrene-butadiene rubber (SBR) / carboxymethyl cellulose (CMC), SBR:CMC=7:3 (weight ratio)) in a weight ratio of 1:1, and then a cathode slurry composition was prepared in which a sulfur-carbon composite (sulfur:porous carbon material=75:25 (weight ratio)), a binder, and reduced graphene oxide were mixed in a weight ratio (weight%) of 94:5:1.

[0118] The positive electrode slurry composition thus prepared was applied to a thickness of 250 μm on an aluminum foil having a thickness of 20 μm, and then dried at 50° C. for 12 hours to prepare a positive electrode.

[0119] The prepared positive electrode and a lithium metal negative electrode having a thickness of 40 μm were placed facing each other, a separator was interposed between them, and 70 μl of electrolyte was injected to prepare a lithium-sulfur battery.

[0120] The separator was made of polyethylene with a thickness of 16 μm and a porosity of 46%, and the electrolyte was a mixture of 0.75 M LiFSI and 3 wt% lithium nitrate dissolved in an organic solvent made of 2-methylfuran and dimethoxyethane mixed in a volume ratio of 33:77.

[0121] [Example 2] Specific surface area is 1000m 2 A lithium-sulfur battery was manufactured in the same manner as in Example 1, except that a pre-dispersion was prepared by mixing reduced graphene oxide having a weight ratio of 1:1 with a binder (styrene-butadiene rubber (SBR) / carboxymethyl cellulose (CMC), SBR:CMC=7:3 (weight ratio)) and a sulfur-carbon composite (sulfur:porous carbon material=75:25 (weight ratio)), a binder, and reduced graphene oxide in a weight ratio (weight %) of 93.5:5:1.5.

[0122] [Example 3] Specific surface area is 1000m 2A lithium-sulfur battery was manufactured in the same manner as in Example 1, except that reduced graphene oxide having a molecular weight of 1000 to 1500 g / g and a binder (styrene-butadiene rubber (SBR) / carboxymethyl cellulose (CMC), SBR:CMC=7:3 (weight ratio)) were mixed in a weight ratio of 1:1 to prepare a pre-dispersion, and then a positive electrode slurry composition in which a sulfur-carbon composite (sulfur:porous carbon material=75:25 (weight ratio)), a binder, and reduced graphene oxide were mixed in a weight ratio (weight %) of 92:5:3 was prepared.

[0123] [Example 4] Ethanol has a specific surface area of ​​1000m 2 / g of reduced graphene oxide was dispersed to prepare a reduced graphene oxide dispersion (reduced graphene oxide:ethanol=1:99 (weight ratio)).

[0124] The reduced graphene oxide dispersion was mixed with a sulfur-carbon composite (sulfur:porous carbon material = 75:25 (weight ratio)) and then dried to prepare a sulfur-carbon composite having a carbon coating layer containing reduced graphene oxide on its surface. The content of reduced graphene oxide in the coated sulfur-carbon composite was 1 wt%.

[0125] A positive electrode slurry composition was prepared by mixing 95 wt % of the prepared sulfur-carbon composite as a positive electrode active material and 5 wt % of styrene-butadiene rubber / carboxymethyl cellulose (SBR:CMC=7:3, weight ratio) as a binder.

[0126] The positive electrode slurry composition thus prepared was applied to a thickness of 250 μm on an aluminum foil having a thickness of 20 μm, and then dried at 50° C. for 12 hours to prepare a positive electrode.

[0127] The prepared positive electrode and a lithium metal negative electrode having a thickness of 40 μm were placed facing each other, a separator was interposed between them, and 70 μl of electrolyte was injected to prepare a lithium-sulfur battery.

[0128] The separator was made of polyethylene with a thickness of 16 μm and a porosity of 46%, and the electrolyte was a mixture of 0.75 M LiFSI and 3 wt% lithium nitrate dissolved in an organic solvent made of 2-methylfuran and dimethoxyethane mixed in a volume ratio of 33:77.

[0129] [Example 5] Ethanol has a specific surface area of ​​1000m 2 / g of reduced graphene oxide was dispersed to prepare a reduced graphene oxide dispersion (reduced graphene oxide:ethanol=1:99 (weight ratio)).

[0130] The reduced graphene oxide dispersion was mixed with a sulfur-carbon composite (sulfur:porous carbon material = 75:25 (weight ratio) and then dried to prepare a sulfur-carbon composite having a carbon coating layer containing reduced graphene oxide on its surface. The content of reduced graphene oxide in the coated sulfur-carbon composite was 1.5 wt%.

[0131] A lithium-sulfur battery was manufactured in the same manner as in Example 4, except that the sulfur-carbon composite prepared above was used as a positive electrode active material.

[0132] [Example 6] Ethanol has a specific surface area of ​​1000m 2 / g of reduced graphene oxide was dispersed to prepare a reduced graphene oxide dispersion (reduced graphene oxide:ethanol=1:99 (weight ratio)).

[0133] The reduced graphene oxide dispersion was mixed with a sulfur-carbon composite (sulfur:porous carbon material = 75:25 (weight ratio)) and then dried to prepare a sulfur-carbon composite having a carbon coating layer containing reduced graphene oxide on its surface. The content of reduced graphene oxide in the coated sulfur-carbon composite was 3 wt%.

[0134] A lithium-sulfur battery was manufactured in the same manner as in Example 4, except that the sulfur-carbon composite prepared above was used as a positive electrode active material.

[0135] [Comparative Example 1] A positive electrode slurry composition was prepared by mixing 95 wt% of a sulfur-carbon composite (sulfur:porous carbon material = 75:25 (weight ratio)) as a positive electrode active material and 5 wt% of styrene-butadiene rubber / carboxymethyl cellulose (SBR:CMC = 7:3, weight ratio) as a binder.

[0136] The positive electrode slurry composition thus prepared was applied to a thickness of 250 μm on an aluminum foil having a thickness of 20 μm, and then dried at 50° C. for 12 hours to prepare a positive electrode.

[0137] The prepared positive electrode and a 40 μm thick lithium metal negative electrode were placed facing each other, a separator was interposed between them, and 70 μl of electrolyte was injected to prepare a lithium-sulfur battery.

[0138] The separator was made of polyethylene with a thickness of 16 μm and a porosity of 46%, and the electrolyte was a mixture of 0.75 M LiFSI and 3 wt% lithium nitrate dissolved in an organic solvent made of 2-methylfuran and dimethoxyethane mixed in a volume ratio of 33:77.

[0139] [Comparative Example 2] Reduced graphene oxide (specific surface area: 100 m) in ethanol 2 After dispersing 1000g of sulfur in a 1000-ml aqueous solution of 10000g ...

[0140] A lithium-sulfur battery was manufactured in the same manner as in Comparative Example 1, except that the sulfur-carbon composite prepared above was used as a positive electrode active material.

[0141] [Comparative Example 3] Ethanol has a specific surface area of ​​1000m 2 / g of reduced graphene oxide was dispersed to prepare a reduced graphene oxide dispersion (reduced graphene oxide:ethanol=1:99 (weight ratio)).

[0142] The reduced graphene oxide dispersion was mixed with a sulfur-carbon composite (sulfur:porous carbon material = 75:25 (weight ratio)) and then dried to prepare a sulfur-carbon composite having a carbon coating layer containing reduced graphene oxide on its surface. The content of reduced graphene oxide in the coated sulfur-carbon composite was 5 wt%.

[0143] A lithium-sulfur battery was manufactured in the same manner as in Comparative Example 1, except that the sulfur-carbon composite prepared above was used as a positive electrode active material.

[0144] Experimental example 1. The specific surface area, pore volume, pore size, and average particle size of the positive electrode active materials used in the examples and comparative examples were measured.

[0145] Specifically, the amount of nitrogen adsorption and desorption was measured using a specific surface area measuring device (model: BELSORP-MINI, manufacturer: BEL Japan Inc.). From this, an isothermal adsorption / desorption curve was obtained, and the specific surface area was calculated using the BET (Brunaure-Emmett-Teller) equation. In addition, the pore volume and pore size distribution were measured using the BJH (Barrett-Joyner-Halenda) calculation. In addition, the volume average particle size (MV) and average particle size (D) were measured using a particle size distribution measuring device. 10 ) and average particle size (D 50 The results are shown in Tables 1 and 2.

[0146] [Table 1]

[0147] [Table 2]

[0148] As shown in Table 1, the positive electrode active materials of the Examples include a discontinuous carbon coating layer, and thus have improved specific surface areas and pore volumes and smaller pore sizes, compared to the positive electrode active materials of the Comparative Examples including a pure sulfur-carbon composite without a carbon coating layer.

[0149] Also, from Table 2, it can be seen that in the case of the positive electrode active material according to the embodiment, the volume average particle size and the average particle size are smaller than those of the positive electrode active material according to the comparative example.

[0150] Experimental example 2. The positive electrodes prepared in Examples 3 and 6 and Comparative Example 2 were observed with a scanning electron microscope (SEM). At this time, the scanning electron microscope used was Hitachi S-4800, and the results obtained are shown in Figures 2 to 4.

[0151] 2 and 3, the positive electrodes according to Examples 3 and 6 include a positive electrode active material in which a discontinuous island-shaped carbon coating layer is formed on the surface of a sulfur-carbon composite. As a result, the surface covered with reduced graphene oxide and the pores of the porous carbon material included in the sulfur-carbon composite are all visible, and a carbon bridge (region indicated by a dotted line) is present between them.

[0152] Meanwhile, in the case of Comparative Example 2, when a cathode active material having a continuous carbon coating layer formed on the entire surface of the sulfur-carbon composite is included, it can be seen from FIG. 4 that the pores on the surface of the sulfur-carbon composite are completely covered with reduced graphene oxide contained in the carbon coating layer.

[0153] Experimental example 3. The capacity and life characteristics of the batteries manufactured in the examples and comparative examples were evaluated using a charge / discharge measuring device.

[0154] Specifically, the capacity characteristics of the battery were evaluated by discharging the battery at a current density of 0.1 C at 25° C. to 1.8 V and then charging the battery at a current density of 0.1 C to 2.5 V. The results are shown in FIGS.

[0155] In addition, the battery was discharged at 25°C at a current density of 0.1 C to 1.8 V, and then charged at a current density of 0.1 C to 2.5 V, and this process was repeated three times. The battery was then charged and discharged three times at a current density of 0.2 C in the same voltage range, and discharged at a current density of 0.3 C and charged at a current density of 0.2 C to evaluate the battery life characteristics. The results are shown in Table 3, Figures 7 and 8.

[0156] [Table 3]

[0157] 4 and 5 and Table 3, it can be seen that the batteries according to the embodiments have superior capacity characteristics compared to the comparative examples.

[0158] Specifically, referring to FIG. 5, the battery of Comparative Example 1 has an initial discharge capacity of 1050 mAh / g, while the batteries of Examples 2 and 5 have initial discharge capacities of 1162 mAh / g and 1183 mAh / g, respectively, and thus have improved discharge capacities and excellent capacity and output characteristics.

[0159] In addition, it can be seen from FIG. 6 that when the carbon coating layer exceeds 3 wt % (Comparative Example 3), the specific surface area of ​​the positive electrode active material is reduced, resulting in reduced reactivity compared to when no carbon coating layer is formed (Comparative Example 1).

[0160] As shown in FIG. 7 and Table 3, the batteries according to Examples 1 to 6 not only exhibited improved discharge capacity as compared to the battery according to Comparative Example 1, but also had excellent maintenance characteristics.

[0161] In addition, in the case of the positive electrode of Comparative Example 2, in which a continuous carbon coating layer is formed on the entire surface of the sulfur-carbon composite, as shown in FIG. 8, the initial discharge capacity is similar to that of Comparative Example 1. However, since the pore structure of the porous carbon material contained in the sulfur-carbon composite cannot be utilized, the discharge capacity rapidly deteriorates as the cycles proceed, and the life characteristics are inferior. [Explanation of symbols]

[0162] 11: Sulfur-carbon complexes 13: Carbon coating layer 15: Carbon bridge

Claims

1. A positive electrode for a lithium-sulfur battery comprising a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector, The positive electrode active material layer includes a sulfur-carbon composite having a carbon coating layer in the form of multiple islands on a surface thereof as a positive electrode active material, the carbon coating layer comprises reduced graphene oxide; The reduced graphene oxide has a specific surface area of ​​700 m 2 / g or more; The reduced graphene oxide is included in an amount of 0.5 wt % to 3 wt % based on the total weight of the positive electrode active material.

2. The reduced graphene oxide has a specific surface area of ​​700 m 2 / g to 1500m 2 2. The positive electrode for a lithium-sulfur battery according to claim 1, wherein the Li-ion concentration is 1.0:

1.

3. The positive electrode active material has a specific surface area of ​​20 m 2 / g to 50m 2 2. The positive electrode for a lithium-sulfur battery according to claim 1, wherein the Li-ion concentration is 1.0:

1.

4. The positive electrode active material has a pore volume of 0.3 cm 3 / g to 0.5 cm 3 2. The positive electrode for a lithium-sulfur battery according to claim 1, wherein the Li-ion concentration is 1.0:

1.

5. 2. The positive electrode of claim 1, wherein the positive electrode active material has a pore size of 30 nm to 70 nm.

6. 2. The positive electrode of claim 1, wherein a ratio of a specific surface area of ​​the positive electrode active material to a specific surface area of ​​the sulfur-carbon composite not including a carbon coating layer is 1 to 3.

7. 2. The positive electrode of claim 1, wherein the positive electrode active material layer further comprises a carbon bridge connecting the positive electrode active materials.

8. 8. The positive electrode for a lithium-sulfur battery according to claim 7, wherein the carbon bridge is in the form of a wrinkled structure or a fiber.

9. dispersing reduced graphene oxide in a dispersion medium to prepare a reduced graphene oxide dispersion; mixing the reduced graphene oxide dispersion and the sulfur-carbon composite and drying the resulting mixture to prepare a sulfur-carbon composite having a carbon coating layer in the form of multiple islands on its surface; preparing a positive electrode slurry composition including the sulfur-carbon composite having the carbon coating layer; and applying the positive electrode slurry composition to at least one surface of a positive electrode current collector; The reduced graphene oxide is contained in an amount of 0.5 wt % to 3 wt % based on the total weight of the positive electrode active material.

10. The method for producing a positive electrode for a lithium-sulfur battery according to claim 9, wherein the dispersion medium comprises a lower alcohol.

11. preparing a pre-dispersion containing reduced graphene oxide; Adding the pre-dispersion to a mixture containing a sulfur-carbon composite and a binder to prepare a positive electrode slurry composition; and A method for preparing a positive electrode for a lithium-sulfur battery, comprising: applying the positive electrode slurry composition to at least one surface of a positive electrode current collector, The reduced graphene oxide is included in an amount of 0.5 wt % to 3 wt % based on the total weight of the positive electrode active material, The positive electrode for the lithium-sulfur battery includes a positive electrode active material layer located on at least one surface of the positive electrode current collector, the positive electrode active material layer including a sulfur-carbon composite having a plurality of island-shaped carbon coating layers on a surface thereof.

12. 2. The positive electrode for a lithium-sulfur battery according to claim 1; A negative electrode; and A lithium-sulfur battery containing an electrolyte.

Citation Information

Patent Citations

  • Lithium sulfide-graphene oxide composite materials for li / s batteries

    JP2017531284A

  • Method for Preparing Surfur-Carbon Complex Comprising Carbon Coating Layer

    KR1020200064332A

  • KR2016‐0046775

  • Sulfur-carbon composite, method for producing same, and positive electrode for lithium-sulfur battery and lithium-sulfur battery which comprise same

    WO2020009332A1

  • Cathode active material for lithium secondary battery

    WO2020166871A1